2014
DOI: 10.1038/ajg.2014.206
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and the Risk of Barrett's Esophagus: A Pooled Analysis from the International BEACON Consortium

Abstract: Background Results from studies examining the association between alcohol consumption and the risk of Barrett’s esophagus have been inconsistent. We assessed the risk of Barrett’s esophagus associated with total and beverage-specific alcohol consumption by pooling individual participant data from five case-control studies participating in the international Barrett’s and Esophageal Adenocarcinoma Consortium (BEACON). Methods For analysis there were 1282 population-based controls, 1418 controls with gastroesop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 30 publications
4
37
2
Order By: Relevance
“…This association was also observed by Tseng et al in a Taiwanese study 145. Alcohol is not regarded as a risk factor 154 . H. pylori has been shown to be a negative risk factor in both Asia and the Western world 155 156.…”
Section: Resultssupporting
confidence: 76%
“…This association was also observed by Tseng et al in a Taiwanese study 145. Alcohol is not regarded as a risk factor 154 . H. pylori has been shown to be a negative risk factor in both Asia and the Western world 155 156.…”
Section: Resultssupporting
confidence: 76%
“…While our results may not be generalizable to women and non-veterans, because BE disproportionately affects men and whites, the veteran population is adequate to study risk factors for BE. Furthermore, our previously published results from this VA-based study have been generally consistent with results from BE studies conducted in the U.S., Ireland and Australia [5,17,18,25]. …”
Section: Discussionsupporting
confidence: 89%
“…Emerging risk factors include lower gluteofemoral obesity [13] and shorter height [14]. However, studies of BE have reported conflicting results for associations with various other risk factors, including tobacco smoking [15,16], alcohol consumption [15,17], use of nonsteroidal anti-inflammatory drugs (NSAIDs) [18], bisphosphonates [19], as well as contrasting magnitudes of association with “known” risk factors [20]. …”
Section: Introductionmentioning
confidence: 99%
“…Similar mechanisms might also be operating for Barrett's adenocarcinoma and require further study. In contrast, recent analyses have suggested that drinking is not involved in Barrett's carcinogenesis, while others state that appropriate quantities of alcohol can decrease susceptibility to Barrett's adenocarcinoma [20]. Several other conflicting risk factors exist between the conditions.…”
Section: Discussionmentioning
confidence: 89%